Peran BKAD Subosukawonosraten Dalam Kerjasama Antar Daerah - Putranto, Adhitya Eka (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Inter-Region Cooperation Board (BKAD) is a body that coordinates inter-region cooperation to reduce competition based on local ego and at the same time increases competitive advantage in a broader scope. The study examined the role of BKAD Subosukowonosraten in coordination of cooperation among locals in the region formerly known as Karesidenan Surakarta. The study analyzed the institutional form and characteristics, role in the cooperation, and the aspects affecting the cooperation. The study is conducted using qualitative case study approach using snowballing interviews with –Ing Ramto being the first source as one of the first initiators of the cooperation. Analysis indicated a sense of independence of BKAD due to its characteristic as being non structural in conducting its role of coordination, facilitation and evaluation throughout the realization of the cooperation. However, this study found an institutional problem which may potentially constrain its role, namely the presence of structural official inside BKAD. This finding may lead to the moderation of BKAD’s role as the central body in the inter-region cooperation because the presence of structural official tend to reduce its independence.